2004
DOI: 10.1128/cdli.11.6.1189-1191.2004
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Tocopherol-Associated Protein in Mast Cells

Abstract: Tocopherol-associated protein (TAP) was expressed in mouse mast cells. TAP was predominantly localized in the cytoplasm, and the subcellular localization was not changed by ␣-tocopherol. The results suggest that the physiological role of TAP in mast cells is not regulation of tocopherol function but an as-yet-unidentified activity.In general, redox status modulates cellular functions. Oxidation stress activates cellular signaling, including the NF-B pathway and the mitogen-associated protein kinase pathway (2,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 18 publications
(21 reference statements)
1
1
0
Order By: Relevance
“…However, two cell lines appeared to express higher levels of hTAP1 mRNA, the HMC-1 mastocytoma and the H295R human adrenocortical carcinoma cells. In line with the results of Ikeda et al [30], HMC-1 expressed mainly hTAP1 (Fig. 1A).…”
Section: Expression Levels Of Htaps In Hmc-1 Mastocytoma Cells and H2...supporting
confidence: 92%
“…However, two cell lines appeared to express higher levels of hTAP1 mRNA, the HMC-1 mastocytoma and the H295R human adrenocortical carcinoma cells. In line with the results of Ikeda et al [30], HMC-1 expressed mainly hTAP1 (Fig. 1A).…”
Section: Expression Levels Of Htaps In Hmc-1 Mastocytoma Cells and H2...supporting
confidence: 92%
“…This report suggested that TAP might be associated with intracellular metabolism, non-antioxidative function, and the regulation of gene expression of α-Toc [ 92 ]. However, TAP, expressed in mouse mast cells, was predominantly localised in the cytoplasm and its subcellular localisation was not changed by α-Toc [ 93 ]. These results suggest that the physiological role of TAP in mast cells is not α-Toc-related, while as an α-Toc binding protein, TAP can promote α-Toc retention and thus increase its concentration in breast cancer cells [ 94 ].…”
Section: Vitamin E and Ve-related Moleculesmentioning
confidence: 99%